Pengaruh Promosi Kesehatan Berperilaku “Patuh” Menggunakan Leaflet Terhadap Motivasi Dan Upaya Pengendalian Hipertensi (Window of Public Health Journal, 2026)
Hypertension is a significant health problem in the world due to its high prevalence rate and is associated with an increased risk of cardiovascular disease. The increased risk of hypertension is due to a lack of knowledge in hypertension management, causing sufferers to come to health facilities when there are complaints or even when the condition is already severe, such as difficulty in lowering blood pressure or complications such as stroke and kidney failure. This study aims to determine the effect of health promotion behavior "PATUH" using leaflets on motivation and efforts to control hypertension. This study uses a quantitative approach with a pretest-posttest design. The population in this study was 150 people; the sample size, calculated using the Slovin formula, was 109, selected through random sampling. Data were collected via questionnaires, and the Wilcoxon test was used. According to the Wilcoxon test results, with a sig. value of 0.000, indicating a difference before and after the provision of leaflet media education on knowledge, while the Wilcoxon test was used with a significance level. A value of 0.000 indicates a difference before and after the provision of leaflet media education on knowledge, while the Wilcoxon test is significant. A value of 0.000 indicates a difference before and after the provision of leaflet media education on knowledge, and a value of 0.001 shows a difference before and after the provision of leaflet media education on knowledge of respondents at the Kalabbirang Community Health Center, Pangkep Regency, in 2025. The conclusion is that there is a difference before and after the provision of leaflet media education on behavior and motivation.